PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI APLIKASI PT. XYZ - Natasha, Natasha; Yudha, Eka Purna (Universitas Galuh, 2023)
The rapid development of technology makes the world seem to be without barriers. The internet is one of the technological developments that has been utilized by companies to become a medium of trade and buying and selling. This development is also followed by food business platforms precisely on online groceries. The development of the food business is supported by the abundance of agricultural products in Indonesia and the desire of e-commerce players to help farmers market products directly to consumers. PT. XYZ is one of the fast online shopping services in Indonesia where there is a 1-hour delivery service by paying attention to the freshness and accuracy of the products that will be received by consumers. This study used quantitative methods with surveys through simple random sampling techniques and obtained 91 respondents. The data were analyzed using descriptive analysis and multiple regression analysis tests. The results showed that marketing mix variables simultaneously affect consumer purchasing decisions at PT. XYZ. Meanwhile, partially the variables of product, promotion, process,